Navigating the delivery of a service - Wickström, Joel (2021)
In a world where environmental pressure on companies is increasing, environmental consultancy services are a valued commodity. This study set out to investigate environmental consultants’ practice of delivering an environmental service and what obstacles that practice encounters. This was achieved through a qualitative interview study with environmental consultants. The practice perspective was provided by Cook & Wagenaar’s (2012) Epistemology of Practice, comprised of Actionable understanding, Ongoing business and the Eternally unfolding present. Two inductive concepts were also introduced, used here as a tool to reposition the original practice perspectives lens to better illustrate the researched phenomenon.